Efektivitas Penyelesaian Tindak Pidana Ringan Melalui Lembaga Adat (Sarak Opat) - Achmad Surya; Suhartini Suhartini (Fakultas Hukum Universitas Islam Indonesia, 2019)
Thisstudy aims firstly to observe the effectiveness of minor criminal acts settlement through Sarak Opat in Central Aceh District. Second, it is to find out what constraints being faced by Sarak Opat are in settling the minor criminal acts in Central Aceh District. The method used in this study was empirical legal research or sociological legal research. The types and sources of data used in this study included library research and field research. The data analysis technique was conducted through a descriptivequalitative method by analysing the data obtained from the primary and secondary data sources. This was then continued with a thorough discussion and a conclusion, based on the discussion, was drawn in response to the problems studied. The results of the research showed first that it was still ineffective now that the people becoming the victims of criminal acts more believed in the police as the law enforcement officials rather than the settlement through the traditional institution of Sarak Opat. Second,the constraints faced by Sarak Opat in the settlement of minor crimes in Central Aceh Regency, included 1). The lack of understanding of the traditional institution of Sarak Opat; 2). Customary sanctions not giving any deterrent effects on the perpetrator; 3). No documented dispute settlement by traditional institution Sarak Opat; 4). Lack of coordination between traditional institution Sarak Opat and Police Department.